1992
DOI: 10.1007/bf00319156
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in expression of calcitonin gene-related peptide and substance P immunoreactivity in ganglia and fibres following guanethidine and/or capsaicin denervation

Abstract: This study was designed to investigate the effects of multiple denervation procedures on calcitonin gene-related peptide- and substance P-immunoreactive neurons in sympathetic and sensory cranial ganglia and in selected targets. Sympathectomy by long-term guanethidine treatment induced a pronounced increase in calcitonin gene-related peptide-immunoreactive and substance P-immunoreactive nerve fibres in all the tissues investigated, in contrast to a significant reduction of immunoreactive cell bodies. Neonatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

1994
1994
2005
2005

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 37 publications
1
11
0
1
Order By: Relevance
“…This view suggests interplay between sympathetic and sensory nerves to and from WAT respectively, and is based on evidence for such interactions in other tissues. For example, global sympathectomy or surgical denervation markedly increases CGRP immunoreactivity in the mesenteric and other vascular beds, as well as in most organs (Mione et al 1992;Aberdeen et al 1990). Conversely, a reciprocal response occurs after global sensory denervation, resulting in increases in sympathetic activity measured electrophysiologically (Ralevic et al 1995 Fig.…”
Section: Does White Adipose Tissue Have Parasympathetic Nervous Systementioning
confidence: 99%
“…This view suggests interplay between sympathetic and sensory nerves to and from WAT respectively, and is based on evidence for such interactions in other tissues. For example, global sympathectomy or surgical denervation markedly increases CGRP immunoreactivity in the mesenteric and other vascular beds, as well as in most organs (Mione et al 1992;Aberdeen et al 1990). Conversely, a reciprocal response occurs after global sensory denervation, resulting in increases in sympathetic activity measured electrophysiologically (Ralevic et al 1995 Fig.…”
Section: Does White Adipose Tissue Have Parasympathetic Nervous Systementioning
confidence: 99%
“…Similarly, the diminished low flow levels for ATP may represent a long-term effect of sensory denervation on endothelial synthesis and cytosolic levels. According ly, we have previously shown that endothelial cells iso lated from older rabbits release more ET and ATP than younger rabbits and also express more ET immunoreactivity [20], It is of particular interest that there was a greater per fusate flow-stimulated release of SP from the microvessels isolated from capsaicin-treated animals since SP is one of the neuropeptides found in sensory nerves [44], Capsaicin treatment thus leads to a depletion of the neural source of SP from the vasculature [25]. It is tempting to speculate that increased expression of SP in the endothelium of brain microvesseis may be a compensatory mechanism in vessels lacking sensory vasodilatory innervation.…”
Section: Discussionmentioning
confidence: 99%
“…On days 2 and 3 they were carried out under ice anesthesia. This treatment regime has been shown to lead to depletion of SPimmunoreactive nerves from the vasculature including cerebral ves sels [16,25],…”
Section: Capsaicin Treatmentmentioning
confidence: 99%
“…3, 5. 7 and 14 of life) [19]. The treatment was in accordance with statutory regulations for the use of animals in scientific procedures.…”
Section: In Vivo Capsaicin Treatmentmentioning
confidence: 99%